2013
DOI: 10.2489/jswc.68.5.361
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of water nutrient levels associated with forest vegetation in highly altered landscapes

Abstract: Stream pollution by nutrient loading is a chronic problem in the Midwest, United States, and greater impacts on water quality are expected as agricultural production and urban areas expand. Remnant riparian forests are critical for maintaining ecosystem functions in this landscape context, allowing water infiltration and capture of nutrients before they are lost from the system. Our objective was to identify linkages between riparian forest plant community composition and water quality in remnant forested head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Extensive research over the last several decades has indicated development that replaces natural land cover often significantly decreases stream water quality (e.g., Cole, Peierls, Caraco, & Pace, ; Howarth, Fruci, & Sherman, ; Mattikalli & Richards, ; McKee, Eyre, & Hossain, ; McKee, Eyre, Hossain, & Pepperell, ; Meybeck, ). However, studies that have evaluated impacts between urban and agricultural land cover on suspended solid and nutrient concentrations have yielded inconsistent and sometimes contradictory results between various U.S. ecoregions (e.g., Dodds & Oakes, ; Golay, Thompson, Mabry, & Kolka, ; Line, White, Osmond, Jennings, & Mojonnier, ; Miller et al., ; Paul & Meyer, ). In some cases, land cover impacts within a study area can also vary between the water quality parameters that are being examined (e.g., Lenat & Crawford, ; Line et al., ; Vidon et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research over the last several decades has indicated development that replaces natural land cover often significantly decreases stream water quality (e.g., Cole, Peierls, Caraco, & Pace, ; Howarth, Fruci, & Sherman, ; Mattikalli & Richards, ; McKee, Eyre, & Hossain, ; McKee, Eyre, Hossain, & Pepperell, ; Meybeck, ). However, studies that have evaluated impacts between urban and agricultural land cover on suspended solid and nutrient concentrations have yielded inconsistent and sometimes contradictory results between various U.S. ecoregions (e.g., Dodds & Oakes, ; Golay, Thompson, Mabry, & Kolka, ; Line, White, Osmond, Jennings, & Mojonnier, ; Miller et al., ; Paul & Meyer, ). In some cases, land cover impacts within a study area can also vary between the water quality parameters that are being examined (e.g., Lenat & Crawford, ; Line et al., ; Vidon et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…These changes are typically the direct or indirect result of human activity, including cattle grazing, deer overabundance, nonnative earth worms, nonnative plant introductions, and heavy recreational use in urban and suburban areas (e.g., Gibson et al 2000, Mabry 2002, Rooney et al 2004, Andrés-Abellán et al 2005, Nuzzo et al 2009, Cameron et al 2015. Forests that have been subjected to these forms of disturbance, as well as new secondary forests, have fewer native herbaceous species than are present in preserved forests, and instead have understories composed of bare ground or herbaceous plant communities dominated by generalist and invasive species (Mabry 2002, Rooney et al 2004, Gerken et al 2010, Gerken Golay et al 2013b). Consequently, many woodlands across this broad region are unlikely to have a full complement of native understory species.…”
Section: Restoration Recap •mentioning
confidence: 99%
“…For example, the classic Hubbard Brook experiments in central New Hampshire emphasized the functional importance of the understory layer and introduced the vernal dam hypothesis, which suggests that spring-growing understory plants take up significant quantities of nutrients, particularly nitrogen and phosphorus, decreasing nutrient pollution in streams early in the growing season (Muller and Bormann 1976). The importance of nutrient uptake by this layer has been confirmed in numerous additional studies (Blank et al 1980, Peterson and Rolfe 1982, Tremblay and Larocque 2001, Gerken Golay et al 2013b, Gerken Golay et al 2016). In addition, these plants…”
mentioning
confidence: 97%